Growing Trend in Application of Age-Stage, Two-Sex Life Table Theory in Diverse Ecological and Pest Management Studies - Baral, Sabitri; Jha, Ratna K. (Journal of the Plant Protection Society, 2018)
Life table is an effective tool for characterizing the demography of an arthropod to understand the phenomenon in pest population development which is a key for developing IPM strategy. Age-stage, two-sex life tables provide comprehensive insights into the stage differentiation of an arthropods, compared with the traditional female age-specific life tables and any other forms of life tables. The age-stage, two-sex life table approach is applied in diverse type of ecological and pest management research. This article is intended to draw attention of Nepalese researchers towards the significance of demographic studies for development of IPM strategy, advancements in application of age-stage, two-sex life table approach and its computer programs. Altogether more than 694 peer reviewed papers and PhD theses have been published since 1988. Out of this, 92 papers were sampled and reviewed for this paper. In such papers, demography of diverse 50 species of arthropods classified under 27 different families belonging to 10 orders have been studied using this theory to measure their fitness in diverse food and environment condition, to assess their consumption, predation or parasitism capacity and to project their population growth in different scenario, to forecast the timing of control based on the stage structure of pest populations and to be used in mass rearing and harvesting of predators and preys under biological control program.